Depositional record of metal(loid)s since late quaternary in the Laizhou Bay, China - Longlong Liu; Longlong Liu; Junfeng Gao; Shengjiang Zhang; Sen Lin; Dongdong Lu; Jialin Zhang; Xiang Xie; Bin Chen; Jiandong Qiu (Frontiers in Marine Science)
The contamination of marine ecosystems with metal(loid)s is an increasing environmental concern, largely driven by anthropogenic activities, and poses a significant risk to the health of ecosystems and human well-being. Geochemical background values represent the typical concentrations of trace elements observed in the natural environment. The utilization of disparate background values gives rise to disparate evaluation outcomes. The objective of this study was to investigate the concentration profiles of metal(loid)s (Cu, Pb, Zn, Cr, Cd, As, and Hg) along a sediment core in order to obtain background values and assess the depositional processes and contamination levels in Laizhou Bay. With the exception of arsenic, the distribution patterns of the remaining metal(loid)s were similar and could be divided into four stages, which were primarily influenced by the mean grain size and sediment sources. The results of the analysis of multiple indicators indicated that there was no evidence of heavy metal enrichment or contamination in the core sediments. Furthermore, the data demonstrated that all metal(loid)s present were of natural origin. The historical changes in metal(loid)s in the core sediments were predominantly linked to the sedimentary environment, sediment sources, and mean grain size. The mean values of the metal(loid)s in the DU 4-2 unit, formed during the Early Holocene, may be regarded as reference values for background concentrations.